Colonoscopy Leading to the Diagnosis of AL Amyloidosis in the Gastrointestinal Tract Mimicking an Acute Ulcerative Colitis Flare. Issue 11 (November 2019) - Lee, Brian S.; Chudasama, Yuvrajsinh; Chen, Adam I.; Lim, Brian S.; Taira, Mark T.
Abstract : ABSTRACT: The 2 most common types of amyloidosis are light chain (AL) and reactive (AA). AL is associated with plasma cell dyscrasias; reactive (AA) is associated with chronic inflammatory conditions. A few cases have described AL amyloidosis mimicking colitis. However, endoscopic findings leading to the diagnosis of AL amyloidosis are rare. We report a 77-year-old woman with a medical history of ulcerative colitis who presented with recurrent nonbloody watery diarrhea. Colonoscopy revealed features suspicious for amyloidosis. Bone marrow biopsy showed multiple myeloma and AL amyloidosis. This case demonstrates the importance of generating a broad differential and the pivotal role of endoscopic findings in diagnosing uncommon diseases.